Manajemen Lembaga Pendidikan Berorientasi Mutu di SMP Ali Maksum Krapyak Yogyakarta - Achmad Sunani Miftachurrohman; Atika Atika (Jurnal Pendidikan Madrasah, 2018)
AbstractThe quality of education is about two sides of a very important process and results. Quality in the educational process involving various inputs such as; learning materials (cognitive, affective, or psychomotor), methodology (vary according the ability of teachers), educational institutions and infrastructure, administrative support, a variety of resources and efforts of the creation of a fair and convenient to learn. Quality in the context of "educational results" refers to the accomplishments achieved by the institution at any particular period of time. The purpose of this research is to know the management institution-oriented quality, how the model of planning education, a system of organization to carry out the education planning, management of quality control, evaluation of organizing education to development and quality improvement strategies towards the implementation of the education in Ali Maksum Junior High School Krapyak Yogyakarta. The subject of this research is the principal and vice principal of Junior High School curriculum areas Ali Infallible Krapyak. This research uses qualitative descriptive. The results showed that the management of the institution in Ali Maksum Junior High School already quality oriented with demonstrated capabilities leverage existing educational resources, both human resources and to enhance the capabilities of the human input , process and output of education in order to meet the requirements demanded by the users of educational services. The entire management activities in high school the first Ali Maksum Junior High School directed at the demands and satisfaction of customers or users of educational services (stakeholders). Keywords: Quality Management of Islamic Education Institutions AbstrakMutu pendidikan merupakan hal tentang dua sisi yang sangat penting yaitu proses dan hasil. Mutu dalam proses pendidikan melibatkan berbagai input seperti; bahan ajar (kognitif, afektif, atau psikomotorik), metodologi (bervariasi sesuai kemampuan guru), sarana dan prasarana lembaga pendidikan, dukungan administrasi, berbagai sumber daya dan upaya penciptaan suasana yang fair dan nyaman untuk belajar. Mutu dalam konteks “hasil pendidikan” mengacu pada prestasi yang dicapai oleh lembaga pendidikan pada setiap kurun waktu tertentu. Tujuan penelitian ini adalah mengetahui manajemen lembaga pendidikan yang berorientasi pada mutu, bagaimana model perencanaan pendidikannya, sistem organisasi untuk melaksanakan perencanaan pendidikan, manajemen kendali mutu, evaluasi terhadap penyelenggaraan pendidikan sampai strategi pengembangan dan peningkatan mutu terhadap pelaksanaan pendidikan di SMP Ali Maksum Krapyak Yogyakarta. Subyek penelitian ini adalah kepala sekolah dan wakil kepala sekolah bidang kurikulum SMP Ali Maksum Krapyak. Penelitian ini menggunakan deskriptif kualitatif. Hasil penelitian menunjukkan bahwa manajemen lembaga pendidikan di SMP Ali Maksum sudah berorientasi pada mutu dengan menunjukkan kemampuan mendayagunakan sumber daya pendidikan, baik sumber daya manusia maupun non manusia untuk meningkatkan kemampuan input, proses dan output pendidikan guna memenuhi persyaratan yang dituntut oleh pengguna jasa pendidikan. Seluruh kegiatan manajemen di SMP Ali Maksum diarahkan pada tuntutan dan kepuasan pelanggan atau pengguna jasa pendidikan (stakeholders). Kata Kunci: Manajemen Mutu Lembaga Pendidikan Islam